Neue Chance für Scholle und Kabeljau in der Nordsee - Weber, Wolfgang (1995)
Two surveys in the German Bight revealed a relatively good recruitment for plaice and cod. However, with the current high effort and uneconomic way of fishing, most of these fish will end as discards. To protect young plaice during the winter months an increase of the mesh opening in beam trawls within the plaice box is suggested. Therefore, the fishermen are called upon to make a more considerated selection of their nets.